Comprehensive disaster damage management planning and the safety of advanced technologies to improve its efficiency (political and legal aspects) - S. N. Tikhomirov (Юг России: экология, развитие, 2022)
Aim. The author aims to draw attention to the urgent need to accelerate the development of the scientific, technical and organizational basis for solving a global economic problem: reducing damage from natural disasters and, in this context, the issue of security and legal regulation of the use of geophysical technologies for active protection against them.Discussion. The thirty‐year universal campaign conducted by the UN and consisting of special events, did not at any stage bring about the repeatedly planned significant reduction in the number of human victims and the amount of material damage. Its prolonged failure proves that the expected result cannot be obtained due to the attracted potential. In addition, it makes us critically evaluate the chosen means of implementing programmes and look for new ways to increase the effectiveness of the fight against the threat. In the natural sciences, the most promising prospect is methods that are being mastered in many developed countries and focused on a targeted influence on the destructive natural process. In this area, large‐scale scientific work has been carried out for a long time and already productively to increase the capabilities and scope of the modifying effect. However, serious problems arise on the path; they have been caused by insufficient knowledge of the changing natural phenomena, military and environmental aspects of these technologies, low predictability of the long‐term consequences of their use, conflicts between economic interests of different states. From a humanitarian point of view, the scale and dynamics of the adverse natural trend require a more radical and operational response than the implementation of methodological recommendations of a single plan for the widespread dissemination of a safety culture. The form of a collective solution adequate to the importance and significance of the universal task is a global disaster risk management which has a developed institutional base and a solid executive discipline. But it is absent today.Conclusion. It is impossible to overcome the indicated obstacles for raising efficiency except by relying on a special regulatory platform of a universal level, which, however, today consists almost entirely of declarative decisions. Here it is necessary to increase the imperativeness of regulation, giving it legal force which is capable of more than recommendatory one to ensure by 2030 a previously unattainable substantial reduction in losses. It is also necessary to move to binding specific measures and technical standards agreed upon and guaranteed by legal instruments. To what extent the special system of international security created on such a basis will satisfy national interests in the future, depends very much on the degree of state participation in this construction today.